Focusing on the process: experiences and needs of Chinese post-esophagectomy patients and caregivers regarding home enteral nutrition - Liao, Huiyan; Cheng, Muxi; He, Yuxin; Li, Hui; Song, Xinhui; Zhong, Lei; Li, Mei (Frontiers in Nutrition, 2025)
ObjectiveThe benefits of home enteral nutrition for postoperative esophageal cancer patients are well recognized, but there is limited evidence on the experiences and needs of patients and caregivers, particularly in the Chinese context. This study aimed to explore these experiences and identify areas for improvement.MethodsA descriptive qualitative design with purposive sampling was employed. In-depth, face-to-face interviews were conducted with 13 patients and 15 caregivers at a tertiary hospital in Guangdong Province, China, between November 2024 and January 2025. Thematic analysis was performed using NVivo 14.0 software to organize and interpret the data.ResultsFour main themes emerged from the interviews: Experience-related themes included (1) Physical burden, encompassing tube-related discomfort, gastrointestinal symptoms, restricted activity, sleep disturbances, and fatigue; and (2) Psychological dilemma, including sense of insecurity, stigma, and negative emotions. Needs-related themes included (3) Needs for nutritional management knowledge, such as scientific understanding, knowledge of technical skills, nutritional calculation and weight management, and knowledge for dietary transition; and (4) Needs for external social support, including family support, peer support, and continuity of care support, and social policy support.ConclusionThis study emphasizes the physical and psychological challenges faced by patients and caregivers during home enteral nutrition, along with their unmet needs for nutritional management knowledge and external support. Healthcare professionals should provide comprehensive information to assist patient decision-making, discharge planning, and nutritional counseling. Improving patients’ and their caregivers’ nutritional literacy and self-care, and utilizing digital platforms and community resources, are essential for enhancing continuity-of-care services and external support systems.